Prevalence of second hand smoke exposure and measures to overcome: A cross sectional study among youth in Urban Hyderabad - Pavani Varma; Anu Mohandas; Sindhu Rudrashetty; K Satya Vara Prasad; N Balakrishna; Snigdha Pattnaik (Wolters Kluwer Medknow Publications, 2024)
In India, the prevalence of secondhand smoke (SHS) exposure is 29.5% in general and 11.2% at home. The youth may expose themselves to SHS without knowing the risk factors and consequences involved. This study is intended to determine the prevalence of SHS exposure and the measures adopted by the youth to avoid exposure. A cross-sectional study was conducted among 338 youth in an urban area in Hyderabad. A modified Global Youth Tobacco Survey questionnaire was used for data collection on SHS exposure and avoidance. The total prevalence of SHS exposure was 35.21%. The mean days of SHS exposure/week were 1.419 (standard deviation -1.806) days. Belonging to the age group 18-21 years, and male gender were significant predictors of SHS exposure. Education of the head of family was a significant predictor of SHS avoidance behavior. Creating awareness among young adults regarding the deleterious effects and preventive strategies of SHS exposure, thereby making them responsible for the health of their family can be a protective long-term strategy.